Xinyang Tablet attenuates chronic hypoxia-induced right ventricular remodeling via inhibiting cardiomyocytes apoptosis - An-Ran Gao; Shuo Li; Xiao-Cui Tan; Ting Huang; Hua-Jin Dong; Rui Xue; Jing-Cao Li; Yang Zhang; You-Zhi Zhang; Xiao Wang (BMC, 2022)
Abstract Background Hypoxia-induced pulmonary hypertension (HPH) is one of the fatal pathologies developed under hypobaric hypoxia and eventually leads to right ventricular (RV) remodeling and RV failure. Clinically, the mortality rate of RV failure caused by HPH is high and lacks effective drugs. Xinyang Tablet (XYT), a traditional Chinese medicine exhibits significant efficacy in the treatment of congestive heart failure and cardiac dysfunction. However, the effects of XYT on chronic hypoxia-induced RV failure are not clear. Methods The content of XYT was analyzed by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS). Sprague-Dawley (SD) rats were housed in a hypobaric chamber (equal to the parameter in altitude 5500 m) for 21 days to obtain the RV remodeling model. Electrocardiogram (ECG) and hemodynamic parameters were measured by iWorx Acquisition & Analysis System. Pathological morphological changes in the RV and pulmonary vessels were observed by H&E staining and Masson's trichrome staining. Myocardial apoptosis was tested by TUNEL assay. Protein expression levels of TNF-α, IL-6, Bax, Bcl-2, and caspase-3 in the RV and H9c2 cells were detected by western blot. Meanwhile, H9c2 cells were induced by CoCl2 to establish a hypoxia injury model to verify the protective effect and mechanisms of XYT. A CCK-8 assay was performed to determine the viability of H9c2 cells. CoCl2-induced apoptosis was detected by Annexin-FITC/PI flow cytometry and Hoechst 33,258 staining. Results XYT remarkably improved RV hemodynamic disorder and ECG parameters. XYT attenuated hypoxia-induced pathological injury in RV and pulmonary vessels. We also observed that XYT treatment decreased the expression levels of TNF-α, IL-6, Bax/Bcl-2 ratio, and the numbers of myocardial apoptosis in RV. In H9c2 myocardial hypoxia model, XYT protected H9c2 cells against Cobalt chloride (CoCl2)-induced apoptosis. We also found that XYT could antagonize CoCl2-induced apoptosis through upregulating Bcl-2, inhibiting Bax and caspase-3 expression. Conclusions We concluded that XYT improved hypoxia-induced RV remodeling and protected against cardiac injury by inhibiting apoptosis pathway in vivo and vitro models, which may be a promising therapeutic strategy for clinical management of hypoxia-induced cardiac injury.